Formation, Repair, and Genotoxic Properties of Bulky DNA Adducts Formed from Tobacco-Specific Nitrosamines - Lisa A. Peterson (Journal of Nucleic Acids)
4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N′-nitrosonornicotine (NNN) are tobacco-specific nitrosamines present in tobacco products and smoke. Both compounds are carcinogenic in laboratory animals, generating tumors at sites comparable to those observed in smokers. These Group 1 human carcinogens are metabolized to reactive intermediates that alkylate DNA. This paper focuses on the DNA pyridyloxobutylation pathway which is common to both compounds. This DNA route generates 7-[4-(3-pyridyl)-4-oxobut-1-yl]-2′-deoxyguanosine, O2-[4-(3-pyridyl)-4-oxobut-1-yl]-2′-deoxycytosine, O2-[4-(3-pyridyl)-4-oxobut-1-yl]-2′-deoxythymidine, and O6-[4-(3-pyridyl)-4-oxobut-1-yl]-2′-deoxyguanosine as well as unstable adducts which dealkylate to release 4-hydroxy-1-{3-pyridyl)-1-butanone or depyriminidate/depurinate to generate abasic sites. There are multiple repair pathways responsible for protecting against the genotoxic effects of these adducts, including adduct reversal as well as base and nucleotide excision repair pathways. Data indicate that several DNA adducts contribute to the overall mutagenic properties of pyridyloxobutylating agents. Which adducts contribute to the carcinogenic properties of this pathway are likely to depend on the biochemistry of the target tissue.